Behavioral response of the freshwater cyclopoid copepod Eucyclops serrulatus to hydropeaking and thermopeaking in a laboratory flume. Issue 1 (1st January 2018) - Sidler, Daniel; Michalec, François-Gaël; Holzner, Markus
ABSTRACT: The generation of electricity by hydropower plants meets the requirements for intermittent energy demand and for the production of renewable energy. However, the hydropower plant operation has important consequences for the biotic compartment of the river reaches downstream. Intermittent release of water causes sudden variations in discharge that increase bed shear stress and dislodge benthic organisms. Release from high-elevation reservoir can also affect the thermal regime of the river by causing sharp variations in water temperature. Because the hydrodynamic and thermal waves separate while propagating downstream, the benthic community is exposed to two distinct stressors that affect taxa differently based on their sensitivity and adaptations. We investigated separately the effects of a sudden variation in discharge or in water temperature on the small-scale swimming behavior of a widespread species of cyclopoid copepod in a laboratory flume that allows the tracking of organisms both in the water column and in a transparent sediment bed. We gradually varied the discharge or the temperature of the water to mimic the artificial changes caused by hydropower plants. We tracked copepods in three dimensions and quantified the kinematics of their motion. Copepods increased substantially their counter-current swimming effort in response to increasing flow velocity. This behavioral response seems to occur above a threshold in flow velocity of approx. 40 mm/s. It results in a substantial reduction in their downstream transport and hence opposes drift. Copepods reacted differently to warm and cold variations in temperature. Decreasing temperature resulted in a substantially lower counter-current swimming effort, which may therefore increase drift. Rising temperature had no clear effect on their behavior. Our study highlights the importance of understanding the behavioral traits that mediate the response of stream invertebrates to disturbances in the hydraulic and thermal regimes of their environment.